Locating Feminicides: The Geographic Key - García-López, Ernesto (2024)
In Mexico city, feminicide is intertwined with geographical and marginalization factors, concentrating in the most disadvantaged areas of the capital. This study employs the annual geolocation of crime data through the Geographic and Statistical Information System on Gender Violence (SIGEVIG) to correlate marginalization conditions with the locations where feminicides occur. The results reveal essential spatial patterns for understanding the operating modes of this crime as well as the underlying conditions that foster it in specific locations within the city.